Statistical comparison of coverage data of disturbed habitats in the Hajdúság - Szőke, Szilvia; Tanyi, Péter (Acta Agraria Debreceniensis, 2009)
Between 2002 and 2006 we made the coenological survey of five disturbed habitats marked as grasslands. With our coenological examinations and the statistical analyses we wanted to make the detailed botanical survey of the given five habitats in order to verify that the maintenance of habitats amongst agricultural lands – and considered as less valuable – is of high importance and necessary from an environmental point of view, since these habitats are often living and feeding areas of many rare and/or protected plant- and animal species.As a result of the statistical analyses we have pointed out that number of species in case of all the five habitats extreme fluctuation characterizes the statistical universe. As regards theaverage of the coverage it is the highest in case of the third habitat (degraded Puccinellia grassland), and the coefficient of variation shows homogenity as well. In examining the Shannon-value the average is the highest in case of the second habitat (Alopecurus meadow), and the statistical dispersion is the smallest. The coefficient of variation shows medium variability. The median of evenness is the lower in case of the third habitat (degradedPuccinellia meadow) and the statistical is the highest here as well. We have done the Hierarchical and the K-Means Cluster Analyses for the 21 plant associations of the five habitats. Both cluster analyses put the same associations into the same cluster, soone can state that the associations in each cluster are different from the associations of the other ones according to the coverage data of the plant families.